A Bibliometric Analysis of Research on Intangible Cultural Heritage Using CiteSpace - Su, Xinwei; Li, Xi; Kang, Yanxin (SAGE open, 2019)
In recent years, studies on intangible cultural heritage (ICH) have substantially increased as the subject has received extensive attention from scholars. This study collected all the papers (249) on ICH from the Web of Science (WoS) core database. CiteSpace analysis software was used for the bibliometric analysis of all papers, and the results of the analysis of literature clustering, scientific research collaboration, co-citations, and so on were visually displayed. The results show that there is not substantial collaboration among researchers, research institutions, or countries that conduct research on ICH. The relationship between high-yield and high-citation authorship is inconsistent and weak. High-yield countries are mainly concentrated in a small group that includes China, Australia, the United Kingdom, and the United States. The research has mainly focused on heritage protection, heritage space, heritage management, heritage policy, and the internationalization of heritage. In recent years, the focus of research has been on creative heritage tourism, community participation in heritage protection and development, and the authenticity of heritage.